Students’ perception on the adoption of an e-textbook (digital) as an alternative to the printed textbook - Osih, S.C.; Singh, U.G. (South African Journal of Higher Education, 2020)
The debate between using printed textbooks (traditional) or e-textbooks (digital textbooks) is ongoing in the educational sector. Students are often required to buy textbooks in order to complete a course in the university, and this textbook can either be printed or e-textbook. Students who are usually reluctant to read a printed text or electronic texts are not familiar with the advantages and disadvantages of each text, respectively. Thus, the absence of information prompts the students to employ only one kind of text either digital or printed. The purpose of this research was to investigate whether university students prefer printed textbooks or digital textbooks (e-textbooks). The importance of the research is to understand why students are making the decision to use either traditional textbooks or e-textbooks and what makes them develop these preferences. The benefits that will be derived from this research will help illustrate what the students feel about traditional (printed) and e-textbooks (digital) and the choices that go into making that decision. This article is based on a study that was conducted at a university based in Midrand, South Africa. The study applied the mixed methods to analyse the relationship between perceived ease of use (PEOU), perceived usefulness (PU), attitude (ATT), complexity (CMX) and compatibility (CMP) on Behavioural intention to use. Questionnaire was the main data collection tool from as sample of 80 third year students from the Information Technology department of the university in question. The overall result led to the conclusion that students prefer e-textbook to the printed textbook.